Upcycling of black currant pomace for the production of a fermented beverage with Wolfiporia cocos - Sommer, Svenja; Hoffmann, Janine Laura; Fraatz, Marco Alexander; Zorn, Holger; Justus Liebig University Giessen (My University, 2023)
Pomace as a side stream from black currant juice production is mostly discarded, even though it is rich in nutrients like protein, fiber, sugars, anthocyanins, polyphenols, and other secondary metabolites. Fungi from the division of Basidiomycota have a great enzymatic toolbox to recycle these complex mixtures of nutrients. In particular, the edible medicinal fungus Wolfiporia cocos has been described as a suitable biocatalyst to form pleasant aroma compounds in fermentation processes. Therefore, medium optimization, upscaling, and filtration were performed to produce a beverage based on black currant pomace fermented with W. cocos. A trained panel described the beverage as highly pleasant, reminiscent of honey, flowers and berries with a well-balanced sour and sweet taste. The flavor compounds linalool (citrus), geraniol (flowery), phenylacetic acid (honey), methyl phenylacetate (honey), eugenol (clove), and 2-phenylethanol (rose) were produced during fermentation and the concentrations exceeded their respective odor thresholds. The produced beverage was evaluated with 8.0 ± 1.4 from 10 for the question of whether panelists would buy the product. Fungal fermentation with the edible fungus W. cocos enabled the production of a highly pleasant beverage and additionally may reduce waste by using pomace and table sugar as sole ingredients.
Keywords: ddc:540